(untitled) (Scientific journal of the Fergana State University, 2024)
In the study of history, various tools testifying to the distant past - historical works, monuments, monuments, folk legends, inscription stones, household items - are used as historical physical evidence. One such factor is the cave paintings of animals. Cave paintings play an important role in studying the historical life of a certain nation, its ancient way of life, activities, worldview, and psychology. In the history of mankind, domestic and wild animals are tools of labor, helpers and protectors of people, livelihood products, factors that provide them with various products, and are also a means of indicating the past, history, culture and lifestyle of the people. This article describes the symbolic meaning of animals in the history and culture of the world, as well as legends, cave paintings, national customs and traditions of different peoples. In the information presented based on various scientific views and evidence, we can see that real animals in real life and mythological animals in human imagination have deeply penetrated the minds and lifestyles of people since time immemorial. In fact, the images of animals minted on the national currency and ancient coins of different nations, on the facades of ancient monuments, in caves, and the image of animals in religious views and folk mythology speak of a certain history.